Cross-Diagnosis Structural Correlates of Autistic-Like Social Communication Differences. (3rd June 2021) - Kushki, Azadeh; Cardy, Robyn E; Panahandeh, Sina; Malihi, Mahan; Hammill, Christopher; Brian, Jessica; Iaboni, Alana; Taylor, Margot J; Schachar, Russell; Crosbie, Jennifer; Arnold, Paul; Kelley, Elizabeth; et al.
Abstract: Social communication differences are seen in autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and obsessive–compulsive disorder (OCD), but the brain mechanisms contributing to these differences remain largely unknown. To address this gap, we used a data-driven and diagnosis-agnostic approach to discover brain correlates of social communication differences in ASD, ADHD, and OCD, and subgroups of individuals who share similar patterns of brain-behavior associations. A machine learning pipeline (regression clustering) was used to discover the pattern of association between structural brain measures (volume, surface area, and cortical thickness) and social communication abilities. Participants ( n = 416) included children with a diagnosis of ASD ( n = 192, age = 12.0[5.6], 19% female), ADHD ( n = 109, age = 11.1[4.1], 18% female), or OCD ( n = 50, age = 12.3[4.2], 42% female), and typically developing controls ( n = 65, age = 11.6[7.1], 48% female). The analyses revealed (1) associations with social communication abilities in distributed cortical and subcortical networks implicated in social behaviors, language, attention, memory, and executive functions, and (2) three data-driven, diagnosis-agnostic subgroups based on the patterns of association in the above networks. Our results suggest that different brain networks may contribute to social communication differences in subgroups that are not diagnosis-specific.